ENHANCHING STUDENTS’ WRITING SKILL THROUGH MALL: WHATSAPP MESSAGES IN TEACHING WRITING - Sri Wahyuni; Kurnia Febianti (Universitas PGRI Palembang, 2021)
Mobile technologies offer numerous practical uses in language learning. The objective of this study to investigate whether or not the application of whatsapp group could improve students’ English writing achievement. The participant of this study were the second semester of English study program that consisted of 40 students. Quasi – Experimental design was applied in this study. In collecting the data, written test is given to sample. The result of data analysis showed that the students got better improvement in English writing ability after being treated by using Whatsapp Group Discussion. It based on the result of independent t-test whereas the t obtain was 5.298 and the significant level 0.00. Futhermore, it can be concluded that there was a significant difference between the student who were taught by using whatsapp group discussion and those who were not. In other words, Whatsapp group is a good teaching media and strategy in increasing students’ writing achievement. Therefore, it can be said that MALL is an appropriate teaching strategy in teaching writing for EFL students.